P077 Developing a better explanation of osteoarthritis: results from a conjoint analysis of patient preferences. (23rd April 2022) - Paskins, Zoe; Nicholls, Elaine; Grossmann, Heiko; McRobert, Cliona; Peat, George; Shivji, Noureen; Bartlam, Bernadette; Croft, Peter; Jinks, Clare; Maddison, John; Main, Chris; Quicke, Jonathan; et al.
Abstract: Background/Aims: Despite the negative impact of osteoarthritis (OA) and existence of evidence-based guidelines, many patients and professionals lack clarity about the nature of OA and effective treatment strategies. This project aims to improve OA explanations in consultations and investigate the extent to which different explanation statements impact on intention to self-manage OA. Methods: Participants registered at four general practices, aged ≥45 years, with a recorded consultation for OA in the previous two years were mailed a survey. The survey included eight pairs of potential OA explanation statements for participants to select the explanation that would most help them to self-manage their OA, alongside questions on socio-demographics, OA symptoms, comorbidity and health literacy. The OA explanations were designed using a partial-profile choice-based conjoint analysis (profile strength 4, comparison depth 3) from a set of 11 theoretically informed key attributes (Table 1 ). Each attribute contained two statements: one representing current information sources, and one a newly designed statement from our previous co-design work with patients and stakeholders. Results: The survey response rate was 22% (428/1980) (average age = 65 years [SD = 10]; 66% female). The newer statement was preferred to the existing statement for 10 of the 11 statements (indicated by a positive regression coefficient) and 8 of these differences were statistically significant (p < 0.05) (Table 1 ). Sensitivity analyses (e.g. to adjust the model to allow for within person correlation of response, and to test for 2-way interactions between model attributes) did not change the findings from the primary model. Conclusion: Patients with OA preferred the newer statements, with one exception (causes). The preferred statements have been discussed with the project's Patient Advisory Group and the statements combined into a written leaflet and animation, and further assessed using Flesch reading ease and Flesch Grade level. Our conjoint analysis has provided evidence about what explanation statements patients with OA prefer and improve likelihood of self-management. The next step is to evaluate the leaflet and written animation in think-aloud qualitative interviews before refining the OA explanation and widespread dissemination. Disclosure: Z. Paskins: None. E. Nicholls: None. H. Grossmann: None. C. McRobert: None. G. Peat: None. N. Shivji: None. B. Bartlam: None. P. Croft: None. C. Jinks: None. J. Maddison: None. C. Main: None. J. Quicke: None. M. Porcheret: None. J. Protheroe: None. E. Cottrell: None.